7.9k views
4 votes
Enter your answer and show all the steps that you use to solve this problem in the space provided. Simplify the expression. 10 h + 6 − 5 h + 3

User Grender
by
5.3k points

2 Answers

6 votes
Answer: 5h+9


Explanation:

10h+6-5h+3
10h-5h+6+3
5h+6+3
5h+9
User Jordelver
by
5.5k points
1 vote

Answer:

5h + 9

Explanation:

Let's simplify step-by-step.

10h+6−5h+3

=10h+6+−5h+3

Combine Like Terms:

=10h+6+−5h+3

=(10h+−5h)+(6+3)

=5h+9

Answer:

=5h+9

Hope this helps!!! :)

User Jakobhans
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.